Pharmacodynamic characteristics and influencing factors of tapentadol for chronic pain relief under dose titration - Liang Xin; Haoxiang Zhu; Haoxiang Zhu; Suping Niu; Xie Han; Hongxian Pang; Jiangfan Li; Ye Hu; Xuhong Wang; Lujin Li; Lujin Li; Yi Fang (Frontiers in Pain Research)
ObjectiveThe aim of this study was to establish a pharmacodynamic model of tapentadol analgesia under dose titration conditions, to quantitatively analyze the time-effect relationship of the drug, and to identify relevant influencing factors. This model is intended to provide a pharmacodynamic reference for designing rational tapentadol dose titration schemes in clinical research.MethodsRandomized controlled trials assessing the efficacy of tapentadol in the management of chronic pain were retrieved from public databases (PubMed and EMBASE). A time-effect relationship model of the percent change in Numerical Rating Scale (NRS) scores post-tapentadol intervention from baseline was constructed, along with a covariate model to identify factors significantly impacting the analgesic effects of tapentadol. Potential influencing factors that were clinically significant but not included in the final covariate model were examined for their impact trends on tapentadol analgesia through subgroup analysis.ResultsA total of 16 studies involving 4,508 participants were included in the analysis. Covariate analysis indicated that age significantly affected the maximum reduction in NRS scores following tapentadol treatment, with the reduction rate being 40.9% for patients aged 45 and 60.7% for those aged 65, suggesting that older patients have a higher demand for pain relief. Furthermore, studies published after 2014 and placebo-controlled trials showed a slower rate of NRS reduction, indicating a more cautious approach to tapentadol dosing titration post the U.S. opioid crisis and in placebo-controlled contexts. Additionally, subgroup analysis suggested that higher titration doses, higher baseline NRS levels, the use of extended-release tapentadol, and a smaller proportion of male participants were trends associated with better analgesic effects, although the differences were not statistically significant. Moreover, the study found that tapentadol was significantly more effective in treating lower back pain compared to non-lower back pain.ConclusionThis research successfully developed a pharmacodynamic model for dose-titrated tapentadol administration, which can simulate the temporal changes in analgesic effects of tapentadol across different clinical scenarios. This model can guide the formulation of dosing titration protocols for tapentadol in clinical research.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-5-0014/